ORGANIZATIONAL LEADERSHIP MODEL FROM A VUCA PERSPECTIVE (Comparative Study of BUMDes Kujati Perdana Karang Jati and Mitra Mandiri Sentosa Durensewu, Pandaan, East Java) - Muhammad Khafid Ainul Yaqin; Abdul Juli Andi Gani; Romy Hermawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Leaders must influence member behavior as an example of the face of the organization and have the authority to evaluate member performance or make decisions regarding promotion. However, there is no consensus regarding the form, approach and leadership model that is suitable for the VUCA era. In-depth discussions are needed by taking various leadership cases in the VUCA era to find a suitable model. This research compares the Transformational Leadership theory from Bernard M. Bass Bernard M. Bass & Ronald E. Riggio (2006) and Adaptive Leadership from Travis Bradberry & Jean Greaves in (Rohaniah, 2021) in a VUCA perspective, with the aim of developing a leadership model for similar organizations BUMDes. The research results show that the leader of BUMDes Kujati Perdana lacks foresight and lacks use of technology, while the leader of BUMDes Mitra Mandiri Sentosa has strong development ideas, but also uses less technology. Based on this comparison, as argued by Theodore (2003), one of the other benefits of comparison is developing performance indicators. Research produces the concept of Locally Based Leadership which includes innovation, digital thinking, responsiveness, and human development.